Lesson study and the long-term impact on teacher professional community development. Issue 1 (22nd December 2020) - Lewanowski-Breen, Emily; Ni Shuilleabhain, Aoibhinn; Meehan, Maria
Abstract : Purpose: The purpose of this paper is to investigate the long-term impact of participating in school-based lesson study on mathematics teachers' professional community. Design/methodology/approach: A study was conducted with six mathematics teachers, from two post-primary schools in the Republic of Ireland, following up on their participation in school-based lesson study over the academic year 2012/13 (see Ni Shuilleabhain, 2016). Qualitative data were generated through one-to-one, semi-structured interviews with the participating teachers and analysed using an empirical framework for teacher community formation (Grossman et al ., 2001). Findings: Analysis of the interview responses suggests that the mathematics teachers in both schools, Doone and Crannog, had developed a mature professional community during their participation in lesson study in 2012/13. Furthermore, the research finds that, in the absence of any other professional development intervention, both teacher communities have been sustained at this level six years later. These findings suggest that a lesson study may serve as a potential structure to foster the development of sustainable professional communities within subject-based teacher groups. Originality/value: While a lesson study has been shown to support the development of teacher professional communities, previous research has not addressed the sustainability of the communities which emerge. This study, therefore, adds to the existing literature by investigating teachers' perceptions of the long-term impact of lesson study participation on their professional community.